Anti-tumor and immune enhancing activities of rice bran gramisterol on acute myelogenous leukemia - Somsuda Somintara (2018)
Copyright © 2016 Somintara et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background: Acute myelogenous leukemia (AML) is a cancer of the blood that most commonly affects human adults. The specific cause of AML is unclear, but it induces abnormality of white blood cells that grow rapidly and accumulate in bone marrow interfering with the production and functions of the normal blood cells. AML patients face poor prognosis and low quality of life during chemotherapy or transplantation of hematopoietic stem cells due to the progressive impairment of their immune system. The goal of this study is to find natural products that have the potential to delay growth or eliminate the abnormal leukemic cells but cause less harmful effect to the body's immune system. Methods and Findings: The unsaponified fraction of Riceberry rice bran (RBDS) and the main pure compound, gramisterol, were studied for cytotoxicity and biological activities in WEHI-3 cells and in the leukemic mouse model induced by transplantation of WEHI-3 cells intraperitoneally. In the in vitro assay, RBDS and gramisterol exerted sub-G1 phase cell cycle arrest with a potent induction of apoptosis. Both of them effectively decreased cell cycle controlling proteins (cyclin D1 and cyclin E), suppressed cellular DNA synthesis and mitotic division, and reduced anti-apoptosis Bcl-2 protein, but increased apoptotic proteins (p53 and Bax) and activated caspase-3 enzyme in the intrinsic cell death stimulation pathway. In leukemic mice, daily feeding of RBDS significantly increased the amount of immune function-related cells including CD3+, CD19+, and CD11b+, and elevated the serum levels of IFN-γ, TNF-α, IL-2, and IL-12β cytokines, but suppressed IL-10 level. At the tumor sites, CD11b+cells were polarized and became active phagocytotic cells. Treatment of mice normal immune cells with gramisterol alone or a combination of gramisterol with cytokines released from RBDS-treated leukemic mice splenocytes culture synergistically increased pSTAT1 transcriptional factor that up-regulated the genes controlling cell survival and function. Phosphorylation of STAT1 was absent in WEHI-3. Instead, similar treatments significantly decreased pSTAT3 signaling that regulates transcription of genes controlling tumor growth and proliferation. Conclusions: Rice bran gramisterol possesses a promising anti-cancer effect against a tumor of white blood cells and induces the production of anti-cancer immune-related cytokines. Gramisterol induces cell cycle arrest and apoptosis via suppression of pSTAT3 signaling control of tumor cells' growth and progression. Gramisterol increased IFN-γ production and prevented the dysfunctional immune system of leukemic mice by enhancing pSTAT1 transcription signal controlling proliferation and functions of hematopoietic cells in the spleen. Together with IFN-γ, gramisterol efficiently facilitates leukemic mice immune system modulation leading to improvement of the AML condition. Administration of RBDS containing gramisterol potentiates immune recovery of leukemic mice and extends their survival. This finding encourages the medicinal application of rice bran gramisterol as a palliative treatment or an alternative agent for future drug development against AML.